Шевченко та родина Алчевських - Маланій, Олена; Malanii, Olena (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті йде мова про вічні духовні цінності, їх культивацію і наступність у поколіннях українських родин, про значення імені і творчості Т. Шевченка у формуванні національно-культурного вектору «сімейного мікрокосму» шляхетних родів в Україні в кінці ХІХ – на початку ХХ століття на прикладі сім’ї Алчевських, про вплив прогресивних ідей Т. Шевченка на формування національ- ної ідентичності та свідомості молодого покоління українців в умовах Російської імперії. The article refers to the eternal spiritual values, their cultivation and continuity in generations of Ukrainian families about the importance of the name and of Taras Shevchenko in the formation of national and cultural vectors «family microcosm» of noble birth in the Ukraine in the late XIX-early XX century, of undeniable and quite powerful impact of the personality and work of Shevchenko «spiritual aura» Ukrainian nobles family by the example of family Alchevskys about the impact of progressive ideas and creativity Shevchenko on the formation of national identity and patriotic awareness of the younger generation of Ukrainians under Russian Empire. Is traced family tradition family famous Ukrainian Enlightenment and philanthropists Propaganda Shevchenko words in their daily work and creativity. In particular attention is paid to the analysis of of creativity of Christina Alchevska Jr., Ukrainian writer, translator, namely the image of Shevchenko image in her poetry, literary criticism, memoirs.
Shevchenko and family Alchevsky
Keywords: Т. Шевченко; родинні традиції; сімейні історії; мікрокосм; родина Алчевських; Shevchenko; family traditions; family history; a microcosm; family Alchevskys